The enlightened capitalists cautionary tales of business pioneers who tried to do well by doing good - O'Toole, James 1945- (Harper Business, an imprint of HarperCollinsPublishers, 2019)
The pioneers -- The first business reformer : Robert Owen (1771-1858) -- Man with a thousand partners : James Cash Penney (1875-1971) -- The businessman who "cleaned up the world" : William Lever (1851-1925) -- Kisses sweeter than wine : Milton Snavely Hershey (1857-1945) -- Creating an enduring enterprise : James Lincoln (1883-1965) -- New forms of incorporation and governance : John Spedan Lewis (1885-1963), and John Joseph Eagan (1870-1924) -- Johnson & Johnson's rollercoaster ride : Robert Wood Johnson (1893-1968) and james Burke (1925-2012) -- Great genes : Levi Strauss (1829-1902) and his heirs -- Marks & Sparks : Michael Marks (1863-1900) and the Marks and Sieff families -- The golden era -- Leadership as an art : Max de Pree (1924- ) -- Too much of a good thing : William C. Norris (1911-2006) -- Business mavericks : Ken Iverson (1925-2002); Robert Townsend (1920-1998); Herb Kelleher (1931-); Bill Gore (1912-1986) and Terri Kelly (1963-) -- The patricians : Thornton Bradshaw (1917-1988), j. Irwin Miller (1909-2004), Edwin Land (1909-1991), John Whitehead (1922-2015), and Roy Vagelos (1929- ) -- Environmentalists, or capitalists? : Anita Perella Roddick (1942-2007) and Tom Chappell (1943-) -- Lever Redux : Ben Cohen (1951- ) -- Capitalists of a different stripe: Yvon Chouinard (1938- ), Jack Stack (1949- ), Robert Beyster (1924-2014), and others -- Yesterday, today, and tomorrow -- Looking back : what we have learned -- Looking forward : the prospects for enlightened corporate leadership -- Conclusion: difficile est bonum esse -- Endnotes
Includes bibliographical references
Keywords: Unternehmensethik; Unternehmer; Entrepreneurship; USA; Großbritannien